Toluene toxicology: abuse aspects - Forster, Letícia M.K.; Tannhauser, Mario; Tannhauser, Semíramis L. (Revista de Saúde Pública, 1994)
Toluene, present in many industrial and domestic products, is the main solvent involved in solvent abuse and occupational exposure. The main problem in studying toluene-related pathologies is the fact that it is frequently combined with other substances. This review focuses on its potential toxicity. The following subjects are discussed: pharmacologic parameters; physico-chemical features; exposure; clinical trials; experimental research; diagnosis; tolerance and dependence; acute and chronic effects; neurotoxicity; teratogenicity; psychiatric disorders; carcinogenicity; and treatment. It is concluded that is important more research on larger population samples with a view to better definition of the consequences.of chronic use should be undertaken.